Politična udeležba v posocializmu: med deformirano modernostjo, novo modernizacijo in postmodernostjo - Fink-Hafner, Danica (Družboslovne razprave, 2006)
The paper highlights questions of the amount and quality of political participation in post-socialist contexts, especially in Slovenia. On the basis of international comparative studies, previous empirical research in Slovenia and their own public opinion research conducted in 2002 in Slovenia the authors make the following findings: a) the relatively low and declining political participation in the new political system while premodern, modern and buds of post-modern politics still co-exist; and b) the very unequal distribution of social resources and perceptions that support political participation. By analysing public opinion data in Slovenia from 2002 the authors discover six patterns of political participation and the key social barriers of concrete patterns with regard to the respondents' social resources, perceptions of the economy, political system and political orientations.
Keywords: Political participation; Politična participacija; Postsocialism; Postsocializem; Modernizacija; Modernization; Slovenia; Slovenija; postsocialistične države